COMPARATIVE ANALYSIS OF BUSINESS INCOME FOR HYBRID AND NON-HYBRID RICE IN KERUAK DISTRICT, EAST LOMBOK - Sirojuddin Sirojuddin; Rini Endang Prasetyowati (Fakultas Pertanian, Universitas Gunung Rinjani, 2021)
Keruak sub-district was the largest area planted with hybrid rice with an area of ​​140 ha. The community grow hybrid rice because of high production yields of up to 12 tons/ha of dry grain harvest (GKP), far exceeding local or non-hybrid rice production with an average production of 6-7 tons/ha GKP. The purpose of this study was to determine the differences in income and constraints of hybrid rice and non-hybrid rice farming on rice farmers in Keruak District, East Lombok Regency. This study used a descriptive method with a survey technique approach. Site selection by purposive sampling in Batu Putik Village, North Pijot Village and Pijot Village. Determination of respondents by Quota Sampling as many as 60 farmers, namely 30 hybrid rice farmers and 30 non-hybrid rice farmers. The selection of respondent farmers was determined by Proportional Random Sampling. The results showed that the average income received by hybrid rice farmers was Rp. 11,635,027/LLG or Rp. 13.122.210/Ha. As for non-hybrid rice farmers, Rp. 4,388,718/LLG or Rp. 7,278,139/Ha. So the difference between hybrid rice and non-hybrid rice farming income per hectare was Rp. 5,844,071. The results of the analysis of the